Nanosecond Phase Transition Dynamics in Compressively Strained Epitaxial BiFeO3. (31st October 2015) - Cosgriff, Margaret P.; Chen, Pice; Lee, Sung Su; Lee, Hyeon Jun; Kuna, Lukasz; Pitike, Krishna C.; Louis, Lydie; Parker, William D.; Tajiri, Hiroo; Nakhmanson, Serge M.; Jo, Ji Young; Chen, Zuhuang; et al.
Abstract : A highly strained BiFeO3 (BFO) thin film is transformed between phases with distinct structures and properties by nanosecond‐duration applied electric field pulses. Time‐resolved synchrotron X‐ray microdiffraction shows that the steady‐state transformation between phases is accompanied by a dynamical component that is reversed upon the removal of the field. Steady‐state measurements reveal that ≈20% of the volume of a BFO thin film grown on a LaAlO3 substrate can be reproducibly transformed between rhombohedral‐like and tetragonal‐like phases by electric field pulses with magnitudes up to 2 MV cm −1 . A transient component, in which the transformation is reversed following the end of the electric field pulse, can transform a similar fraction of the BFO layer and occurs rapidly time scale limited by the charging time constant of the thin film capacitor. The piezoelectric expansion of the tetragonal‐like phase leads to a strain of up to 0.1%, with a lower limit of 10 pm V −1 for the piezoelectric coefficient of this phase. Density functional theory calculations provide insight into the mechanism of the phase transformation showing that imparting a transient strain of this magnitude favors a transformation from rhombohedral‐like to tetragonal‐like phase. Abstract : A highly strained BiFeO3 thin film is transformed between phases with distinct structures and properties by nanosecond‐duration applied electric field pulses. The steady‐state transformation between phases is accompanied by a dynamical component that is reversed upon the removal of the field. Density functional theory calculations reveal that a transient piezoelectric strain favors a transformation from the rhombohedral‐like to the tetragonal‐like phase.